The Impact of BRI Micro Credit on Financial Literacy and Green Sustainability of MSMEs in North Luwu - Ferdyan, Andre; Hartawan, Luthfi Riza (Research Horizon, 2024)
The potential of MSMEs in Indonesia is significant, contributing substantially to GDP and employment provision. However, MSMEs face various challenges, especially in access to capital and business sustainability. This study aims to analyze the impact of BRI microcredit distribution on the financial literacy of customers in North Luwu Regency and how it supports the sustainability of green MSMEs towards Golden Indonesia 2045. The research employs a mixed-methods approach, combining qualitative and quantitative methods. Data were collected through surveys and in-depth interviews with MSME customers in North Luwu Regency. The results of the study are expected to provide an overview of how BRI microcredit has improved financial literacy and supported the green sustainability of MSMEs in the region. This research also aims to provide policy recommendations for better MSME development and financial literacy improvement in the future.